ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN DI RUMAH MAKAN SFA STEAK & RESTO KARANGANYAR - Putri, Ciciek Adhias; Trisnowati, Juni (Surakarta Management Journal, 2021)
Business in the culinary field has shown quite rapid development. This was marked by the establishment of various types of restaurants in Indonesia. The restaurant is not only a place to eat, but also serves as a place to gather, socialize, exchange ideas, expand networks and also become one of the places for prospecting business. So it can be concluded that eating habits outside the home have become an inseparable part of the life of modern society. In this research, the aim is to determine the effect of product quality, service quality, and price on customers satisfaction in sfa steak and resto karanganyar. the hypothesis in this study are suspected by product quality, service quality, and price have a significant effect on consumers satisfaction in sfa steak & resto karanganyar.necessary data in this study are primary data obtained by questionnaire from a sampel of 100 respondents. analysis of the data used in this research is multiple linier regression test, t test, f test, and the coefficient of determination test.  The result of data analysis in this study can be concluded that of product quality, service quality, and price significantly influence consumers satisfaction in sfa steak & resto Karanganyar.